Resiliencia Urbana, Impacto De La Ronda Hídrica Del Rio Las Ceibas De La Ciudad De Neiva. (Bulevar Rio Las Ceibas) - Muñoz Morales, Sergio Duván (Universidad Antonio Nariño, 2021)
This academic work investigates the urban informality on the riverbed of Las Ceibas in communes 2, 3 and 5 of the municipality of Neiva, proposes an urban resilience which will make the sector rehabilitate the strip of environmental preservation and promote the recovery of public space , against the deterioration caused by the informal settlements located on the water ring of the Las Ceibas river in the sector. Analyze its main components, characteristics, causes and consequences using as a point of reference the environmental deterioration of the Ceibas river caused by the informal settlements of the sector. Academically, an urban project is being carried out on the preservation and recovery of both the environment and the public space of the municipality; carrying out different analyzes at macro and meso scales which include road system, environmental system among others, where it allows to conclude the current potentialities and problems regarding the department and municipality. After this, 4 problem analyzes originate from the intervention polygon located by the water ring of the Ceibas river, encompassing communes 2, 3 and 5, from these problem analyzes, proposals are proposed in the areas: social, economic, environmental and urban. , where it allows to conclude the projects that will finally be carried out through a sectoral urban proposal, intervening in the public space with architectural proposals and urban furnishings, also recovering the environmental axis that was deteriorating due to the location of the informal settlements and thus provide a better relationship between river and city.